Sistem Pendukung Keputusan Penerimaan Bantuan Sembako Menerapkan Metode Moora Studi Kasus : Desa Pulo Sanggar - B, M Tawaf Akbar; Nasution, Ahmad Fahreza (Jurnal Sains dan Teknologi Informasi, 2024)
The impact of food package assistance and direct cash assistance on the survival of people who are classified as incapable. The purpose of this study is to find out and analyze basic food assistance that has an influence on the survival of underprivileged communities. The results of the research on basic food assistance are very influential, so in this case the local government should increase basic food assistance appropriately, considering the survival of residents who are underprivileged and can no longer earn money to finance their lives. Based on the assessment of such criteria, decision makers are faced with difficult problems and tend to rely on subjectivity. In this study, a system was produced that adapts the Moora method.